Very High Density (>1014 cm−2) Polarization‐Induced 2D Hole Gases Observed in Undoped Pseudomorphic InGaN/AlN Heterostructures. (5th January 2022) - Chaudhuri, Reet; Zhang, Zexuan; Xing, Huili Grace; Jena, Debdeep
Abstract: High hole densities are desired in p‐channel field effect transistors to improve the speed and on‐currents. Building on the recently discovered undoped, polarization‐induced GaN/AlN 2D hole gas (2DHG), this work demonstrates the tuning of the piezoelectric polarization difference across the heterointerface by introducing indium in the GaN channel. Using careful design and epitaxial growths, these pseudomorphic (In)GaN/AlN heterostructures result in some of the highest carrier densities of >10 14 cm −2 in a III‐nitride heterostructure—just an order below the intrinsic crystal limit of ≈10 15 cm −2 . These ultra‐high density InGaN/AlN 2DHGs show room temperature mobilities of 0.5–4 cm 2 V −1 s −1 and do not freeze out at low temperatures. A characteristic alloy fluctuation energy of 1.0 eV for hole scattering in InGaN alloy is proposed based on the experiments. Abstract : Herein, a very high density 2D hole gas with densities >10 14 cm −2 is observed in molecular beam epitaxy‐grown, pseudomorphic InGaN/AlN heterostructures. In the absence of chemical dopants, these are generated by the polarization difference at the InGaN/AlN heterointerface. The high piezoelectric polarization in the strained InGaN layer leads to some of the highest charge densities observed in III‐nitride heterostructures.